Can a human capital-based six factor model perform better than Fama-French five factor model: an empirical study on asset pricing in Pakistan - Zada, Hassan; Khan, Naveed; Afeef, Mustafa; Ahmed, Shakeel (2024)
This study compares the human capital based six factor model with the Fama-French five factor model in the context of Pakistan. For this purpose, we collected data from 170 non-financial firms listed on the Pakistan stock exchange based on market capitalization from 2010 to 2020. We employed Fama-Macbeth two-pass approach. This study finds that the six-factor model outperforms the five-factor model of Fama and French to explain variations in portfolio returns. The findings motivate investors and academicians to include human capital as a factor in asset pricing models to improve the estimation of the required rate of return of a security and or portfolio.